2016
DOI: 10.3109/03009742.2015.1132760
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in genomics in lupus: girls with systemic lupus have high interferon gene expression while boys have high levels of tumour necrosis factor-related gene expression

Abstract: Our results suggest a potential application of genomics to differentially predict response to therapy between females and males with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We have previously shown that the response to CpG and R848 stimulation in terms of upregulation of ISGs, CXCL10, and CD86 is type I IFN/STAT-2-dependent, while IL-12, IL-6, and TNF- α were regulated in a type I IFN/STAT-2-independent manner [ 47 ]. A previous study of pediatric SLE patients reported an IFN signature in both female and males [ 6 ] while a recent study of treatment-naïve girls and boys with childhood onset SLE further described a “TNF signature” present in boys but absent in girls [ 78 ], suggesting that sex may affect disease differently by promoting type I IFN-dependent and type I IFNs-independent pathways. Recent studies have also shown that prior to diagnosis of SLE, there is elevated type II IFN in the serum of patients [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the response to CpG and R848 stimulation in terms of upregulation of ISGs, CXCL10, and CD86 is type I IFN/STAT-2-dependent, while IL-12, IL-6, and TNF- α were regulated in a type I IFN/STAT-2-independent manner [ 47 ]. A previous study of pediatric SLE patients reported an IFN signature in both female and males [ 6 ] while a recent study of treatment-naïve girls and boys with childhood onset SLE further described a “TNF signature” present in boys but absent in girls [ 78 ], suggesting that sex may affect disease differently by promoting type I IFN-dependent and type I IFNs-independent pathways. Recent studies have also shown that prior to diagnosis of SLE, there is elevated type II IFN in the serum of patients [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In both mice and humans, estrogen and ER signaling is found to modulate the expression of immunostimulatory cytokines and exacerbates disease activity in lupus mouse model and in human patients [ 43 ] . Previous studies indicated the influence of male and female sex hormones on immune cell functions in SLE [ 44 ] . Particularly estrogen plays a pivotal role in functional modulation of T and B cells and their immune functions.…”
Section: Influence Of Sex Hormones and Receptors In Slementioning
confidence: 99%